Setting large- and medium-sized mammal restoration goals in a last mountain Chaco remnant from central Argentina - Daniel Renison; Harold Rusbelth Quispe-Melgar; G. A. Erica Cuyckens; Ana M. Cingolani (Ecological Processes, 2023)
Abstract Background Setting large- and medium-sized wild mammal (≥ 2 kg) restoration goals is important due to their role as ecosystem engineers and generalized numeric reductions. However, determining wild mammal restoration goals is very challenging due to difficulties in obtaining data on current mammal density and due to unclear information on what mammal density values should be used as a reference. Here we chose a 154 ha conservation area within one of the last remnants of the mountainous Chaco from central Argentina. We suspected that extensive and unreported defaunation had occurred due to past human pressure and the introduction of non-native mammals. To conduct the analyses, we used a simplified technique that integrates methods used in rangeland and ecological sciences. Results Eight native mammal species including only one herbivore species, and four non-native mammal species including three herbivore species were detected during 6113 camera trap days. We used known cattle densities as estimated by droppings and direct counts, together with the relative abundance indexes obtained from camera trap photos to calculate the densities of the other species, correcting for mammal size. Densities for the least and most abundant native species were 0.2 and 1.33 individuals km−2, respectively; and for non-native species, 0.03 and 5.00 individuals km−2, respectively. Native and non-native species represented 0.8% and 99.2%, respectively, of the biomass estimates. Reference values for native herbivore biomass, as estimated from net primary productivity, were 68 times higher than values estimated for the study area (3179 vs. 46.5 kg km−2). Conclusions There is an urgent need to increase native mammals, with special emphasis on herbivore biomass and richness, while non-native mammal numbers must be reduced. As cattle are widespread in large portions of the globe and there is a lot of experience estimating their abundances, the ratio method we used extrapolating from cattle to other large- and medium-sized mammals could facilitate estimating mammal restoration goals in other small and defaunated areas, where traditional methods are not feasible when target mammal densities get very low.